Pejuheşi der bare-yi mektubat-i tarihî-yi Farsi İran ve Maveraunnehr : Safeviyan, Uzbekan ve İmarat-i Buhara : hemrah ba gozize-yi mektubat = Persian Historical Epistles from Iran and Mawara an-nahr the Safavids, the Uzbeks, and the Mangits with an edition of selected epistles - Sefatgol, Mansur. (Tukiyu)
586, 5 s.